Cryogenic Accelerated Fatigue Tester for additive manufactured polymer composite mechanical property measurement. Issue 1 (1st May 2022) - Adams, R; Hunt, M; Leachman, J
Abstract: Additive manufacturing (AM) of polymer matrix composite (PMC) materials maintains the potential to significantly reduce part count, weight, and costs for future aerospace development. However, a lack of maturity in loading systems has inhibited the characterization of these materials for the cryogenic environment of space. These PMCs demand lifespan endurance when faced with cryogenic thermal cycling in series with high-frequency mechanical loading. Few mechanical testers have been capable of achieving the cryogenic temperatures and actuating frequency to simulate the environment that a PMC endures in a cryogenic application. Also, these testers have yet to define the tensile and fatigue PMC mechanical behavior at these temperatures. To curate a cryogenic, fatigue profile on PMCs, the Cryogenic Accelerated Fatigue Tester (CRAFT) was developed. CRAFT utilizes a 12-kN load frame in unison with a cryocooler to perform tension-tension and tension-compression fatigue tests up to 100 Hz in a liquid hydrogen environment. This publication reviews the CRAFT design and capabilities. Determining the cryogenic fatigue life of 3D-printed PMCs through testing in CRAFT allows for the validation of proper material implementation and the future optimization of these materials in cryogenic environments.